2016
DOI: 10.7883/yoken.jjid.2015.121
|View full text |Cite
|
Sign up to set email alerts
|

The First Case of Deceased Donor Liver Transplantation for a Patient with End-Stage Liver Cirrhosis Due to Human Immunodeficiency Virus and Hepatitis C Virus Coinfection in Japan

Abstract: SUMMARY:We previously reported that progression of liver cirrhosis is quicker and survival is dismal in patients with human immunodeficiency virus (HIV) and hepatitis C virus (HCV) coinfection, especially when acquired in childhood through contaminated blood products. Recently, we performed the first deceased donor liver transplantation (DDLT) for an HIV/HCV-coinfected hemophilic patient in Japan. A 40-year-old man was referred to our hospital for liver transplantation. Regular DDLT was performed using the pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…HCV reinfection in the graft liver showed unusual progression, probably due to the presence of HIV with immunosuppression and the hepatotoxicity of previous anti-HIV drugs. [22][23][24] However, because of the advent of DAA, HCV infection could be well controlled without the adverse effects previously seen after interferon/ribavirin therapy. 25 Recently, it has been reported that DAA treatment is very effective for patients co-infected with HCV/HCV before and after LT in Germany.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCV reinfection in the graft liver showed unusual progression, probably due to the presence of HIV with immunosuppression and the hepatotoxicity of previous anti-HIV drugs. [22][23][24] However, because of the advent of DAA, HCV infection could be well controlled without the adverse effects previously seen after interferon/ribavirin therapy. 25 Recently, it has been reported that DAA treatment is very effective for patients co-infected with HCV/HCV before and after LT in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…In the earlier era without DAA treatment, the results of LT were rather dismal even with interferon/ribavirin therapy, with recurrent HCV‐related liver cirrhosis. HCV reinfection in the graft liver showed unusual progression, probably due to the presence of HIV with immunosuppression and the hepatotoxicity of previous anti‐HIV drugs 22–24 . However, because of the advent of DAA, HCV infection could be well controlled without the adverse effects previously seen after interferon/ribavirin therapy 25 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, outcomes for HCC in this population have been reported to be generally poor (5,6). Although surgery, including liver transplantation (LT) (7,8), has been reported as feasible in hemophilic patients, physicians might hesitate to refer such patients not only to surgery, but also to less invasive procedures such as radio frequency ablation (RFA).…”
Section: Introductionmentioning
confidence: 99%